User Model Enrichment for Venue Recommendation - Aliannejadi, Mohammad; Mele, Ida; Crestani, Fabio (Information Retrieval Technology, 2016)
An important task in recommender systems is suggesting relevant venues in a city to a user. These suggestions are usually created by exploiting the user’s history of preferences, which are, for example, collected in previously visited cities. In this paper, we first introduce a user model based on venues’ categories and their descriptive keywords extracted from Foursquare tips. Then, we propose an enriched user model which leverages the users’ reviews from Yelp. Our participation in the TREC 2015 Contextual Suggestion track, confirmed that our model outperforms other approaches by a significant margin.